2005
DOI: 10.2113/jeeg10.2.77
|View full text |Cite
|
Sign up to set email alerts
|

MASW, The Wave of the Future Editorial

Abstract: Revolutionary innovations in geophysical methods develop when instruments, techniques, or software evolve to make them possible. A few of these cause dramatic changes in the types of surveys and analysis done. Past examples were shallow reflection surveys and scanning resistivity pseudo-sections. The author believes that surface wave surveys will cause a similar, perhaps extraordinary paradigm shift in geophysics because of the usefulness and interpretability of the data, and the potential for dramatically hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…The test is repeated a number of times for different geometrical configurations. Crice (2005) acknowledges the usefulness of SASW but suggests that solutions are neither unique nor trivial and that an expert user is required for interpretation. Lo Presti et al (2003) and Soccodato (2003) compared V s derived from SASW with that obtained from other techniques for Pisa clay and Fucino clayey soil respectively.…”
Section: Masw Technique Surface Wave Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test is repeated a number of times for different geometrical configurations. Crice (2005) acknowledges the usefulness of SASW but suggests that solutions are neither unique nor trivial and that an expert user is required for interpretation. Lo Presti et al (2003) and Soccodato (2003) compared V s derived from SASW with that obtained from other techniques for Pisa clay and Fucino clayey soil respectively.…”
Section: Masw Technique Surface Wave Analysis Methodsmentioning
confidence: 99%
“…Advantages of this method include the need for only one-shot gather and its capability of identifying and isolating noise. Crice (2005) illustrates how MASW survey data can be reliably interpreted by computer software without human intervention. The authors have found that this is only accurate for simple soil profiles.…”
Section: Masw Technique Surface Wave Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SASW method uses a single pair of receivers with an impulsive source and should be repeated several times for different soil/geophone configurations. Although the effectiveness of the method has been verified by many researchers, an expert user is needed to interpret the data (Crice [14]). …”
Section: Masw Methodsmentioning
confidence: 99%
“…The four are: compression wave, called the P-wave, shear wave called the Swave, Rayleigh wave and Love wave. P and S waves are known as body waves; Rayleigh and Love waves are surface waves as shown in Figure 1 [10]. A seismic wave transmits energy by the vibration of soil particles in different directions.…”
Section: Introductionmentioning
confidence: 99%